Municipal solid waste management decision-making during COVID-19 pandemic: a comparison between Brazil and Portugal (Research, Society and Development, 2022)
Decisions related to waste management were affected to contain the advance of the new coronavirus pandemic. Different measures have been adopted between countries around the world. This study aims to assess changes in decision-making on solid waste management in Brazil and Portugal during the COVID-19 pandemic, considering the socioeconomic differences and the context of waste management in each country before the health crisis. A literature review was carried out on scientific bases, PubMed, Google Scholar and Web of Science. Differences were noted in decisions and guidelines for good practices in waste management, with measures being observed in a decentralized manner in Brazil, differently from what was observed in Portugal. In this way, the understanding of urban waste management during the COVID-19 pandemic in Brazil becomes complex, in addition to the territorial extension and the diverse social composition, due to the decentralization of decision-making, while Portugal centralizes decisions related to waste management and has a smaller population and territorial extension.